The Tendency to the Syntactic Origin of the Composition - Al-Rashidi, Median Awwad (Dirasat: Human and Social Sciences, 2025)
Objectives: This research aims to interpret the absence of case endings caused by verbal factors in certain documented examples from Arab speakers. It seeks to explain this phenomenon by proposing that the speaker tends to revert to the original syntactic structure before the influence of grammatical factors, thus ignoring these factors. As a result, the sentence appears as if these factors are nonexistent, presenting the sentence in its original nominative structure. Method: This study follows the steps of the descriptive-analytical method, which is based on induction and deriving conclusions through analyzing and interpreting observations. Results: The research demonstrated that grammarians adhered strictly to the necessity and inevitability of grammatical rules, leading them to link syntactic structures to interpretations dictated by these rules. It also found a strong connection between the mental origin associated with speech before the influence of grammatical factors and the presence of case endings in many syntactic structures documented from Arab speakers. Conclusion: The research concluded that grammarians made efforts to individually interpret such anomalous examples without attempting to unify them under a single interpretation, which is what this research has achieved.